Incorporating Quaternary Prevention: Understanding the Full Scope of Public Health Practices in Sexual Abuse Prevention - McCartan, Kieran (International journal of offender therapy and comparative criminology, 2023)
This discussion piece argues for a refinement in our understanding of prevention in sexual abuse, suggesting that we include quaternary prevention on the grounds that this concept from medical literature has potential and helpful application to criminal justice and particularly to work with those who cause sexual harm. Located within the paradigm of Epidemiological Criminology (EpiCrim), quaternary prevention extends the prevention spectrum to enable a stronger distinction between tertiary level responses and long-term safe, sustainable reintegration into communities, particularly of those who sexually abuse others. The key principles of quaternary prevention are adapted and refined from current medical literature, and the potential usefulness of quaternary prevention to crime and sex abuse prevention is explored.